“I Better Not to Speak”: Micro-Culture and Identity Conflict of Female Muslim Students in Language Learning Classroom - Sueb, Sueb; Hartanti, Lina Purwaning; Susanti, Arik (STAIN Majene, 2023)
This study investigates the identity conflict experiences of four female Muslim students involved in persuasive speech activities of a persuasive speech activity as part of Public Speaking course. The research aims to explore the micro-culture phenomena within the classroom, i.e. identity conflicts faced by the participants, strategies for identity negotiation, and the role of strategic investment in language learning. Case study approach was employed using purposive sampling based on classroom reflections at the end of the academic term to determine the participants. In-depth interviews were conducted with the selected participants in a confidential one-on-one setting. The findings contribute to understanding the relationships of micro-culture, identity conflicts and negotiation, and strategic investment in the context of language learning. The research highlights reflective process in relation to the experiences of female Muslim students and provides implications for creating inclusive and safe space for learning environments.